Allergy and contact lenses - Ambroziak, Anna M.; Szaflik, Jerzy (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2009)
Ocular allergy and contact lens wear affect a large percentage of the population, the implications for interaction of allergy and changes induced by contact lens wear are significant. To present all about allergic conditions in general and ophthalmic allergies in particular, and how these can affect contact lens wear. It suggests solutions that can be followed in order to alleviate problems that can arise during contact lens use and suggests ways of overcoming the allergic symptoms and signs. Studies proving the healthiest and the most comfortable way of contact lens wear is the daily disposables are also presented. Nowadays allergy has become an increasing worldwide problem. It is actually a very complex disease in which symptoms can appear without clinical signs and sometimes it is too difficult to isolate the real cause of it. Environment and in some cases it is everyday increasing pollution is thought to be the main cause of allergy development. Just to note that we now have in our houses or near us, more domestic animals and more indoor potted plants. Atmospheric pollution is also a significant cause of allergies, the pollution by tobacco, the problem with the ozone layer and the NO2 concentration in the atmosphere. There is also more domestic pollution with dust, acarid and diesel motor. Allergies have also been noted to have genetic components. For everyone allergies, symptoms, clinical signs and complications are very similar. For contact lens wearer allergy creates a comfort reduction, a wearing time reduction, dryness problems, itchyness and lens awareness symptoms, that would lead at the end to contact lens drop-outs, patients who cease contact lens wear. Ocular allergy occurs due to eye exposure to environment, with ocular conjunctivitis to capture the 5% of all allergy cases. Other ocular events that could initiate an allergy are: viral conjunctivitis, conjunctivitis due to chlamydia, ocular trauma, eye dryness, long-term ultraviolat radiation exposure, the use of cosmetics and reaction to medications. All allergy cases are compare with ocular surface damage and dry eye and this is the basic and significant problem in contact lens wearers.